KAJIAN AKADEMIS DALAM PERTIMBANGAN PENYUSUNAN UPAH - Diana Fajarwati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2010)
In order to provide a unified view in terms of wage determination, the Board has the task of recommending equal pay wages to the Mayor to get the governor setting. Many things need to be assessed in terms of wage determination because without we realize that each element has different interests, so that academic research is needed to be realistic setting of wages for workers, employers and government sides.